Tree-ring δ18Ocellulose variations in two Nothofagus species record large-scaleclimatic signals in the South American sector of the Southern Ocean - Soto Rogel, Pamela; Aravena, Juan Carlos; Villalba, Ricardo; Meier, Wolfgang; Grießinger, Jussi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)
In recent decades, southernmost South America (50–56° S) has experienced marked climate change (regional warming, decreased precipitation, reduced snow cover, and increased frequency of heat waves) related to variations in atmospheric circulation over varied timescales. In this paper, we develop oxygen isotopes from tree-ring cellulose (δ18OTRC) as a proxy for climate and atmospheric circulation in order to extend the regional meteorological record to deeper time intervals. Our work focuses on Nothofagus forests in two areas: (i) deciduous N. pumilio forest in the steppe transition zone near Punta Arenas and (ii) humid evergreen N. betuloides forest in the Navarino Island region. To investigate the potential for reconstructing palaeoclimate, δ18OTRC variations were correlated with local climate parameters as well as regional (Amundsen Sea Low, ASL) and hemispheric (Antarctic Oscillation, AAO) atmospheric circulation modes for the last 60 years. N. betuloides δ18OTRC variations show an overall positive trend, indicating isotopic enrichment over the study period, whereas no trend is recorded for the N. pumilio record. The strongest relationships with climate, together with the widest spatial representativeness, occur in the N. betuloides chronology during the growing season (spring to austral summer) and extend spatially from mid to high latitudes. In contrast, the sensitivity of the records is limited to summer months, and spatial correlations are much more limited. In addition, the N. betuloides record shows greater potential for reconstructing local climate features such as soil water (r = − 0.76), wind speed (r = 0.69), and precipitation (r = − 0.66), as well as regional (ASL, r = − 0.80) and hemispheric (AAO, r = 0.77) patterns of extratropical atmospheric circulation. Overall, we conclude that the N. betuloides record represents the most valuable tree-ring climate proxy for southernmost South America over past centuries.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Amundsen Sea Low (ASL); Antarctic Oscillation (AAO); Nothofagus betuloides; Nothofagus pumilio; Southernmost South America (SSA); Tree-ring δ

Two Nothofagus Species in Southernmost South America Are Recording Divergent Climate Signals - Soto Rogel, Pamela; Carlos Aravena, Juan; Villalba, Ricardo; Bringas, Christian; Meier, Wolfgang; Gonzalez-Reyes, Alvaro; Grießinger, Jussi (Forests, 2022)
Recent climatic trends, such as warming temperatures, decrease in rainfall, and extreme weather events (e.g., heatwaves), are negatively affecting the performance of forests. In northern Patagonia, such conditions have caused tree growth reduction, crown dieback, and massive die-back events. However, studies looking at these consequences in the southernmost temperate forest (Nothofagus betuloides and Nothofagus pumilio) are much scarcer, especially in southernmost South America (SSA). These forests are also under the influence of the positive phase of Antarctic Oscillation (AAO, also known as Southern Annular Mode, SAM) that has been associated with increasing trends in temperature, drought, and extreme events in the last decades. This study evaluated the growth patterns and the climatic response of eight new tree-ring chronologies from Nothofagus species located at the upper treeline along different environmental gradients in three study areas: Punta Arenas, Yendegaia National Park, and Navarino Island in SSA. The main modes of the ring-width index (RWI) variation were studied using principal component analysis (PCA). We found that PC1 has the higher loadings for sites with precipitation values over 600 mm/yr, PC2 with N. betuloides sites, and PC3 with higher loadings for sites with precipitation values below 600 mm/yr. Our best growth-climate relationships are between N. betuloides and AAO and the most northeastern site of N. pumilio with relative humidity (which coincides with heatwaves and extreme drought). The climatic signals imprinted in the southernmost forests are sensitive to climatic variability, the climate forcing AAO, and the effects of climate change in the last decades.
CRIS-Team WoS Importer:2022-06-10